Implications Of The Abolition Of The Presidential Threshold For The Realization Of Substantial Democracy - Achmad Hariri (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
The implementation of the presidential threshold (PT) in Indonesia’s electoral system has been a significant topic of debate in national politics. PT, which requires political parties or coalitions to meet a certain vote threshold to nominate a presidential candidate, is considered an instrument to strengthen political stability. However, critics argue that PT limits voter choice, benefits major parties, and hinders the realization of a more substantial democracy. This article aims to analyze the implications of abolishing PT for achieving substantial democracy, which emphasizes openness, broad participation, and equality in the political process. The findings of this discussion indicate that the implementation of PT in Indonesia restricts political representation, marginalizes small parties and independent candidates, and reduces voter choice diversity. Although PT aims to strengthen political stability by encouraging coalitions, it risks undermining inclusive democracy. The varying number of presidential candidates in 2004 (5 candidates), 2009 and 2024 (3 candidates), as well as 2014 and 2019 (2 candidates), demonstrates PT’s impact on political competition. More candidates provide greater choices but can fragment votes, whereas fewer candidates simplify elections but reduce inclusivity. Abolishing PT could create opportunities for more candidates, fostering a more inclusive and competitive environment, but it may also lead to political fragmentation and difficulties in coalition formation. Therefore, a balanced reform between inclusivity and political stability is necessary to enhance the quality of democracy in Indonesia.